2011
DOI: 10.1111/j.1365-2664.2011.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter from insect‐resistant transgenic trees causes changes in aquatic insect community composition

Abstract: Summary1. Recent research has addressed how transgenic residues from arable crops may influence adjacent waterways, aquatic consumers and important ecosystem processes such as litter breakdown rates. With future applications of transgenic plants in forestry, such concerns may apply to forest stream ecosystems. Before any large-scale release of genetically modified (GM) trees, it is therefore imperative to evaluate the effects of genetic modifications in trees on such ecosystems. 2. We conducted decomposition e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Existence of outliers in the data was tested using box plots whereas normality was tested using the Kolmogorov-Smirnov test and homogeneity was tested using the Leven's test (Nienhuis & Stout, 2009). Whenever normality was not fulfilled, data were log 10 (x+3/8) transformed to achieve normal distributions (Axelsson et al, 2011; SAS Resource on the web, 2012). All the aforementioned statistical analyses were done in MS Excel and Minitab 14 software at the 95% confidence level.…”
Section: Discussionmentioning
confidence: 99%
“…Existence of outliers in the data was tested using box plots whereas normality was tested using the Kolmogorov-Smirnov test and homogeneity was tested using the Leven's test (Nienhuis & Stout, 2009). Whenever normality was not fulfilled, data were log 10 (x+3/8) transformed to achieve normal distributions (Axelsson et al, 2011; SAS Resource on the web, 2012). All the aforementioned statistical analyses were done in MS Excel and Minitab 14 software at the 95% confidence level.…”
Section: Discussionmentioning
confidence: 99%
“…Nontarget effects of other Bt-plants (Populus spp.) were also reported for aquatic biota (Axelsson et al, 2011a(Axelsson et al, , 2011b.…”
mentioning
confidence: 99%
“…By-products from GM plants (e.g., pollen, detritus) can be transported in water courses to downstream water bodies where non-target aquatic arthropods can be exposed to transgene product(s) through consumption (Axelsson et al, 2010(Axelsson et al, , 2011. In the case of Bt-maize, Rosi-Marshall et al (2007) reported that by-products of Bt-maize enter headwater streams in the United States and claimed, on the basis of experimental data obtained under lower-tier conditions, that this would reduce growth and increase mortality of some non-target aquatic arthropods, especially trichopteran species (see also Chambers et al, 2010;Tank et al, 2010).…”
mentioning
confidence: 99%